(3GdGbJUGO GdHfcj (B:s (3eONd eYGUQ (B/s - (3Ndjd, YHO GdbGOQs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2017)
(3jbOe cJGH (B"(3GdEbJUGO GdeYQaj eONd eYGUQ(B" (3QDjI JMdjdjI eYebI ddeUGQa hOhQgG aj GdEbJUGO GdeYGUQ, MjK Je JZWjJg YHQ SHYI aUhd, JfGhd ajgG GdJehjd hEYGOI GdJehjd, eY EYWGA deMI Mhd GdeUGQa, dfeQ Edi JMdjd JHjjV GdCehGd GdPj jSJNOe GdeUQa cbfGI dPdc, Ke OQS GdUjQaI GdEdcJQhfjI, eY EYWGA Cge GdefJLGJ hGdCShGb GdeUQajI, hHYO Pdc JWQbfG ddEJLGgGJ GdMOjKI aj eLGd GdNOeGJ GdeUQajI, djNJJe gPG GdYed HJfGhd GdYhdeI hGdJMQjQ GdeGdj(B.s
(3GdeQGLY U(B.155 (3CSFdI eNJGQI ef eSGHbGJ OcJhQGg d(B.(3e(B.(3O U(B.165 (3GdCTcGd U(B.177s
Keywords: (3GdEbJUGO GdHfcjs